2005
DOI: 10.1007/bf03173558
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of students’ school-identification in secondary vocational education

Abstract: This article reports on a study regarding the school-identification of 1819 first-year students in secondary vocational education. We measured the school-identification of these adolescents and used the perspective of self-regulation to define three blocks of potential determinants, including the students' personal goals (1) their appraisals of the school and classroom (2), and their peer-and home-identities (3). One other block included students' personal characteristics, such as general ability (i.e., course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Results indicated that girls and students from regular (non-vocational) courses experienced better home environments and had higher resilience levels and impulse control. These results are consistent with previous research, which reported lower self-regulation skills for boys and students who attended vocational courses (Buckner et al, 2009;García del Castillo & Dias, 2009;Jonker et al, 2010;Koning & Boekaerts, 2005;McCabe & Brooks-Gunn, 2007). Nevertheless, the existence of gender-related differences in resilience is not consensual in the literature, with some studies indicating that girls and boys react differently to adversity and others concluding that no differences between adolescent girls and boys exist (for a review, see Coleman & Hagell, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results indicated that girls and students from regular (non-vocational) courses experienced better home environments and had higher resilience levels and impulse control. These results are consistent with previous research, which reported lower self-regulation skills for boys and students who attended vocational courses (Buckner et al, 2009;García del Castillo & Dias, 2009;Jonker et al, 2010;Koning & Boekaerts, 2005;McCabe & Brooks-Gunn, 2007). Nevertheless, the existence of gender-related differences in resilience is not consensual in the literature, with some studies indicating that girls and boys react differently to adversity and others concluding that no differences between adolescent girls and boys exist (for a review, see Coleman & Hagell, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…At social level, some studies indicate a negative correlation between self-regulation and peer rejection, problematic or antisocial behaviours with peers (Tangney, Baumeister, & Boone, 2004;Trentacosta & Shaw, 2009), but a positive correlation with the involvement and inclusion in the community (Stenseng, Belsky, Skalicka, & Wichstrøm, 2014;Stillmand & Baumeister, 2013). At school level, self-regulation has been positively related to school achievement (Boekaerts, 2005;Duckworth & Seligman, 2005;McClellan & Cameron, 2011;Zimmerman, 1990) and higher levels of self-regulation have been found in students from regular or non-vocational courses when compared to students who attend vocational courses (Jonker, Elferink-Gemser, Toering, Lyons, & Visscher, 2010;Koning & Boekaerts, 2005).…”
Section: From Protective Factors To the Mediating Role Of Self-regulamentioning
confidence: 99%
“…In accordance with these theoretical propositions regarding the psychological mechanisms through which mastery goal structures engender mastery goals, an extensive body of empirical evidence supports the robust link between mastery goal structures and students' mastery goals (for a meta-analytic review, see Bardach et al under review). Nonetheless, while mastery goals and how they relate to educational outcomes have previously been investigated in vocational education (e.g., de Koning and Boekaerts 2005), the link between mastery goals and mastery goal structures has not yet been addressed. Vocational education prepares students for different professions.…”
Section: The Relation Between Mastery Goal Structures Personal Mastementioning
confidence: 99%